The complete mitochondrial DNA sequence of the green algae Hariotina sp. F30 (Scenedesmaceae, Sphaeropleales, Chlorophyceae). Issue 1 (1st January 2016) - He, Lijuan; Lou, Sulin; Zhang, Fang; Yang, Shanjun; Zhang, Chao; Lin, Xiangzhi; Yang, Longhe
Abstract: The complete mitochondrial genome of the green algae Hariotina sp. F30 was obtained in this study using Illumina sequencing data. It is 51 915 bp in length with 36.23% GC content. The genome contains 13 protein-coding genes, 23 tRNA genes and six rRNA genes, all of which are encoded on the heavy strand. AUG is a universal initiation codon among 13 protein-coding genes. UCA is a universal termination codon for most protein-coding gens except UAA in cox1 and cob genes and UGA in nad6 gene. CUU anticodon for tRNA-Lys was detected for the first time in Sphaeropleales.